INTERSTRAIN DIFFERENCES IN EMOTIONAL AND WEIGHT INDICES IN GC RATS WITH CATATONIC RESPONSE AND WISTAR RATS - T. A. Alekhina; R. V. Kozhemjakina (Вавиловский журнал генетики и селекции)
In selecting rats for behavior, we observe a direct natural effect and affect the nonspecific stress function. In this process, new behavioral phenotypes appear in the strain under selection. They differ from the selected forms in the selection criterion. In the GC strain, a large proportion of the so-called nervous rats emerge. The criterion presumes the selection for the long cataleptic freezing character, whereas the nervous rats display elevated motor excitement: running, jumping, and vocalization. The main purpose of our study was to assess phenotypic indices in GC rats (abbreviated from genetic and catatonia) and recognize principal components of variability for emotional and weight indices. Rats of the ancestral Wistar population were taken as control. The following indices were measured: time of cataleptic freezing, excitement level, blood pressure, acoustic startle response, seizure  activity, and weights of the heart, kidneys, adrenals, and spleen. Multivariate analysis methods were applied: factor analysis and principal component analysis. We confirmed the inclination of GC rats of the generation studied to freezing in quiet surrounding and after a strong acoustic sti - mulus. More pronounced startle responses,  moderate hypertension, and larger weights of the heart and adrenals were noted. Two principal variability components were recognized: startle amplitude (PC1) and morphofunctional variability (PC2). The figure shows different locations of Wistar and GC individuals in principal component coordinates. The principal component method confirmed the genetic relationship between the startle and nervousness responses. It was shown that in PC2 the indices of heart, kidney, adrenal, and spleen weight exert negative effects, whereas the effects of startle and nervousness were positive. In the same component, an increase in the startle and nervousness responses positively correlates with the relative weights of the heart and adrenals. Differences in the directions of the contributions to the second component of morphofunctional variability are discussed.